2022
DOI: 10.1155/2022/3977289
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Correlation Analysis of DNA Methylation in the von Willebrand Factor Promoter Region and the Risk of Unexplained Recurrent Hemophilia: Systematic Review and Meta‐Analysis

Abstract: This study systematically reviewed the effect of DNA methylation in the promoter region of the coagulation factor vWF gene on the risk of unexplained recurrent hemophilia. PubMed, Medline, Web of Science, and other computers were used to search the database, and the statistical randomized controlled trials of coagulation factor vWF in the risk analysis of unknown recurrent hemophilia were collected. The Cochrane systematic evaluation method was used to evaluate the quality of the included kinds of literature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%